2016
DOI: 10.5125/jkaoms.2016.42.5.251
|View full text |Cite
|
Sign up to set email alerts
|

Which factors are associated with difficult surgical extraction of impacted lower third molars?

Abstract: ObjectivesThe aim of this retrospective study was to investigate factors associated with increased difficulty in the surgical extraction of impacted lower third molars and to improve identification of difficult cases.Materials and MethodsA total of 680 patients who required 762 surgical extractions of impacted lower third molars from 2009 to 2014 were enrolled in the study. Demographic factors, clinical factors, radiographic factors, surgical extraction difficulty, and presumed causes of difficulty were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…According to many authors, age is the most consistent factor in determination of surgical difficulty because of the difference in bone density. 1,8,9,17 In this study, age was not a statistically significant determinant of surgical difficulty but it may be significant to the occurrence of complications. 4 Renton T, Smeeton N and…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…According to many authors, age is the most consistent factor in determination of surgical difficulty because of the difference in bone density. 1,8,9,17 In this study, age was not a statistically significant determinant of surgical difficulty but it may be significant to the occurrence of complications. 4 Renton T, Smeeton N and…”
Section: Resultsmentioning
confidence: 53%
“…Gender is one of the predictors of difficulty of impacted third molar surgery. 17,19 There is a statistically significance relation between gender and surgical duration which was also noted in the study undertaken by Susarla and Dodson 16 and Sundus AM, Maha MA, Khawlah TH,Ahmed SA. 19 However many studies are not in favor of this.…”
Section: Resultsmentioning
confidence: 55%
“…1,8,9,17 In this study, age was not a statistically significant determinant of surgical difficulty but it may be significant to the occurrence of complications. 4 surgery.…”
Section: Discussionmentioning
confidence: 53%
“…Kyengluk Park 17 in study of 762 surgical extraction, showed impaction side in jaw was statistically not significant.…”
Section: Discussionmentioning
confidence: 94%
“…[1] There are some classification methods for determining surgical difficulty in the literature. Pederson proposed a difficulty index for the removal of mandibular third molars, [2,4,7] and Pederson scale scores are based on local anatomy and radiographs, [2,10] while the modified Parant scale is used to estimate surgical difficulty postoperatively based on the surgical conditions. [2] Previous studies in the literature have set out to identify factors associated with postoperative pain, swelling, and trismus.…”
Section: Introductionmentioning
confidence: 99%